Peran Kode Etik Advokat Dalam Menjamin Penegakan Keadilan di Indonesia - Hidayah, Muhammad Hafiz Fajar; Mahtum, Rohikim; Syahrani, Fiarinda Putri; Chasnun, Faiz Nayla (Media Hukum Indonesia (MHI), 2024)
The enforcement of justice in Indonesia requires the central role of advocates as one of the main pillars in the legal system. In this context, the advocate code of ethics is a fundamental element that serves as a moral and professionalism guideline to ensure advocates perform their duties ethically, transparently, and responsibly. This research examines the role of the advocate code of ethics in maintaining professional integrity, protecting client rights, supporting a fair legal process, and building public trust in the legal system.  The advocate code of ethics not only functions as a supervisory tool, but also provides a sanction mechanism for violations. By prioritizing the values of justice, advocates are required to provide legal services to all parties, including the underprivileged, as mandated by the constitution and laws and regulations. In addition, the advocate code of ethics supports the creation of a just legal system, ensuring that advocates do not pursue profit alone, but act for the sake of justice and equality before the law. Through this study, it is revealed that the existence of an advocate code of ethics is very important in linking the role of advocates as legal aid providers with the achievement of justice. The professionalism and integrity of advocates can be measured based on the extent to which they adhere to the professional code of ethics. Thus, the advocate code of ethics is an important instrument in ensuring the quality and public trust in the legal system in Indonesia.